The Difference of PEFR Value between Brick Making Workers and Farmers in Sitimulyo Piyungan Bantul - Gilda Ditya Asmara; Eddy Surjanto; Yusup Subagyo (Nexus Kedokteran Klinik, 2012)
Background: Workplace that processes release dust and smoke, can cause a reduction of working comfort, visual disturbances, impaired lung physiology, and even can cause general poisoning. Brick making industry is one of the industries that produce a lot of pollution. Pollution resulting from the burning of wood and rice husk as the main fuel. This study aimed to determine the differences in peak expiratory flow rate values among brick making workers by the farmers in the Sitimulyo that not exposed to pollution in the workplace Methods: This study is observational analytic with cross sectional design. This research located in Sitimulyo Piyungan Bantul. There are 33 brick making workers and 33 farmers in Sitimulyo for sampling subjects. The independent variables in this study are the brick making workers and farmers while the dependent variable is the value of peak expiratory flow rate. Peak expiratory flow rate values were measured directly using a peak flow meter and analyzed by Mann-Whitney test.. Results: The results on research with 33 samples of brick making workers and 33 farmers in the Sitimulyo obtained average peak ekspiration flow rate value for brick making workers is 441 L / min or 75.30% of the predicted value of peak ekspiration flow rate and the farmers group was 483 L / min or 82.01% of the predicted value of peak ekspiration flow rate. Then through the mann-whitney test obtained p = 0.015 (p <0.05). From these data showed there is statistically significant difference between the peak ekspiration flow rate value of brick making workers and farmers in Sitimulyo Piyungan Bantul.. Conclusions: There is a statistically significant difference between the peak ekspiration flow rate value of brick making workers and farmers in Sitimulyo Piyungan Bantul. Keywords: PEFR, brick, workers, farmers, Sitimulyo.